Levels of Urinary Trypsin Inhibitor and Structure of Its Chondroitin Sulphate Moiety in Type 1 and Type 2 Diabetes - Antonio Junior Lepedda; Gabriele Nieddu; Silvia Rocchiccioli; Nadia Ucciferri; Michela Idini; Pierina De Muro; Marilena Formato (Journal of Diabetes Research)
Background. Diabetes mellitus is a global health problem representing the fifth leading cause of mortality and a major risk factor for cardiovascular diseases. In the last years, we reported an association among urinary trypsin inhibitor (UTI), a small proteoglycan that plays pleiotropic roles in many inflammatory processes, and both type 1 and 2 diabetes and developed a method for its direct quantitation and structural characterization. Methods. Urine from 39 patients affected by type 1 diabetes, 32 patients with type 2 diabetes, and 52 controls were analysed. UTI was separated from the main glycosaminoglycans physiologically present in urine by anion exchange chromatography, treated for chondroitin sulphate (CS) chain complete depolymerisation, and analysed for both UTI content and CS structure. UTI identification was performed by nano-LC-MS/MS analysis. Results. We evidenced increased UTI levels, as well as reduced sulphation of its CS moiety in association with diabetes, regardless of both age and medium-term glycaemic control. Furthermore, no association between UTI and albumin excretion rate was found. Conclusions. Evidences suggest that UTI levels are not directly correlated with renal function or, otherwise, that they may increase before the onset of renal impairment in diabetes, representing a potential marker for the underlying inflammatory condition.